EPISTEMOLOGI PENDIDIKAN ISLAM DALAM PEMIKIRAN FAZLUR RAHMAN - Kurniawan Syah Putra (Lembaga Sepercenter, 2025)
This study discusses the epistemology of Islamic education in the thinking of Fazlur Rahman, a contemporary thinker who has made many important contributions to the reconstruction of Islamic thought. The main focus is on the concept of double movement, which forms the methodological basis of Fazlur Rahman's understanding of the Qur'an, as well as its implications for Islamic education. This study uses a qualitative approach with a literature review method of Fazlur Rahman's works, especially Islam and Modernity and Islam. The results of the study show that Fazlur Rahman offers a critical, dynamic, and contextual epistemology of Islamic education, which emphasises the importance of integrating the normative values of the Qur'an with the needs of modern humans. Islamic education, according to him, should not only emphasise religious rituals, but also produce individuals who are moral, rational, and capable of responding to the challenges of the times.